Implementation of Health Technology Assessment in the Middle East and North Africa: Comparison Between the Current and Preferred Status - Fasseeh, Ahmad; Karam, Rita; Jameleddine, Mouna; George, Mohsen; Kristensen, Finn Børlum; Al-Rabayah, Abeer A.; Alsaggabi, Abdulaziz H.; El Rabbat, Maha; Alowayesh, Maryam S.; Chamova, Julia; Ismail, Adham; Abaza, Sherif; et al. (Frontiers in Pharmacology, 2020)
INTRODUCTION Implementation of health technology assessment (HTA) is still in the early stage with some heterogeneity in ‎the Middle East and North Africa (MENA). Our objective was to assess the current and future status of HTA implementation in ‎the MENA by ‎focusing on regional commonalities.‎ METHODS Preparatory discussions for the first ISPOR conference in the MENA region indicated some potentially generalizable trends of HTA roadmaps. To widen the perspective, a policy survey was conducted among conference participants by applying an HTA implementation scorecard. Discussion group members helped to validate key conclusions during and after the conference. RESULTS Health policy experts in MENA countries would like to facilitate HTA implementation and expect significant changes with some generalizable directions in 10 years compared to the current status according. HTA capacity building has to be strengthened by more graduate and postgraduate programs. Increased public budget and enhanced institutionalization are necessary success factors of HTA implementation. The scope of HTA has to be extended from pharmaceuticals to non-pharmaceutical technologies and to revision of previous policy decisions. Although cost-effectiveness with explicit threshold remains the most preferred HTA criterion, several other criteria have to be considered, maybe even by applying an explicit MCDA framework. The role of local evidence and data has to be strengthened in MENA countries, which translates to the extended use of local patient registries and payers’ databases. Duplication of efforts can be reduced if international collaboration is integrated into national HTA implementation. ‎DISCUSSION Our results should be viewed as an initial step in a multi-stakeholder dialogue on HTA implementation. ‎Each MENA country should develop its context-specific HTA roadmap, as such roadmaps are not ‎transferable without taking into account country size, economic status, public health ‎priorities and adopted systems of health care financing.‎